Assessment of In-Depth Transport and Retention of Zinc Oxide Nanoparticles Using a Coreflood Approach - Hamza, M.F. (Springer Science and Business Media B.V., 2021)
The study is aimed at investigating the in-depth migration and retention of ZnO nanoparticles (NPs) used in enhanced oil recovery. The nanofluid (0.03) was prepared according to a standard procedure of dispersing the NPs in brine. The hydrodynamic diameter and zeta potential (Î¶) were investigated to ascertain the aggregation and stability of the NPs in brine, respectively. The flooding scenarios were maintained throughout at 0.2Â mLÂ minâ1 flow rate and started by injecting 2 pore volume (PV) of brine followed by 3 PV of nanofluid and lastly another 3 PV of brine post-flush. The effluents were collected at around every 0.2 PV to ascertain the NPs breakthrough, while the pressure drop (âp) across the core was recorded to assess the in-depth migration and retention of the NPs. The rockâs permeability (K) and porosity (É¸) before and after the flooding was investigated to further ascertain the impairment of the rock properties due to possible retention of the NPs. The results of the âp show that nanofluid could generate âp of 109 Â± 19Â mbar slightly higher than the waterflood baseline (107 Â± 12Â mbar) due to structural disjoining pressure resulting from spreading of the NPs in the core. However, large âp (210 Â± 29Â mbar) was noticeable after brine post-flush signifying trapping of the NPs in the porous media. The NPs effluent concentration profile shows that a breakthrough had occurred after injecting 1.53 PV having a lower concentration than the initial injection. Further analysis of K and É¸ after the NPs injection revealed that the K and É¸ had reduced by 52 and 23.3, respectively due to the NPs trapping. These observations could be related to high aggregation (415 Â± 34Â nm) of the ZnO in brine with moderate stability of â 35 Â± 3Â mV as described by the Î¶. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.